Designing and Administering a Needs Analysis Survey to Primary School Learners about EFL learning: a Case Study - Tzotzou, Maria (Preschool and Primary Education, 2014)
Needs analysis is a distinct and necessary phase in planning educational programs and curriculum development. It is used to collect information about learners’ needs, focusing on the study of learners’ perceived and present needs, as well as their potential and unrecognized needs. The purpose of this study was to develop, design and administer a needs analysis survey to a group of primary school learners in order to investigate their attitudes towards EFL learning, their actual foreign language needs and their learning preferences regarding activities, topics and modes of work in the EFL classroom. According to the survey findings derived from the questionnaire used as a research tool, learners’ actual EFL needs, learning styles and strategies are not satisfactorily consistent or compatible with the current teaching situation. As a result, implications which focus on: a more learner-centered teaching methodology and materials, a ‘process-based’ curriculum development and action research in the Greek school context, as well as teacher’s further training education and professional development will be discussed.